2019
DOI: 10.1136/bmjsem-2019-000572
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity counselling in Ireland: a survey of doctors’ knowledge, attitudes and self-reported practice

Abstract: ObjectivePhysical activity (PA) counselling has been shown to raise awareness of the importance of PA and to increase the rate of PA engagement among patients. While much attention has been paid to examining the knowledge, attitudes and practice of general practitioners in relation to PA counselling, there is less literature examining such issues in hospital-based doctors in Ireland and further afield. This study aimed to explore doctors’ PA counselling practices and to analyse how this related to their level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
1
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 26 publications
3
32
1
9
Order By: Relevance
“…In this survey most respondents were fully qualified with regular patient contact for more than 6 years, which suggests that continuing education/professional development on physical activity promotion will be crucial to maximise their impact on and support for sustained behaviour change with their patients. This finding is consistent with other studies that have highlighted the need for postgraduate training for healthcare professionals to address health behaviour change [ 23 , 24 ], but also the need to integrate physical activity training and its relationship with health at an undergraduate level. Several reports indicate that this issue is now receiving greater attention in undergraduate curricula [ 25 , 26 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this survey most respondents were fully qualified with regular patient contact for more than 6 years, which suggests that continuing education/professional development on physical activity promotion will be crucial to maximise their impact on and support for sustained behaviour change with their patients. This finding is consistent with other studies that have highlighted the need for postgraduate training for healthcare professionals to address health behaviour change [ 23 , 24 ], but also the need to integrate physical activity training and its relationship with health at an undergraduate level. Several reports indicate that this issue is now receiving greater attention in undergraduate curricula [ 25 , 26 ].…”
Section: Discussionsupporting
confidence: 92%
“…The recently introduced Making Every Contact Count (MECC) strategy places the responsibility for providing brief (and opportunistic) interventions on all healthcare professionals who may have patient contact in Ireland and Northern Ireland. By integrating MECC at the initial/undergraduate level it is planned that brief interventions will become central to many consultations [ 23 ]. In this survey most respondents were fully qualified with regular patient contact for more than 6 years, which suggests that continuing education/professional development on physical activity promotion will be crucial to maximise their impact on and support for sustained behaviour change with their patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although considered an important part of treatment, nurses, nursing assistants and physicians did not consider mobility as part of their core tasks [ 19 ]. Additionally, as opposed to physicians educated in geriatric specialties, who focused on mobility, physicians educated in medical specialties primarily focused on diagnosis, treatment and discharge of the patient, indicating that their medical education influences their view on what is considered part of their core tasks [ 19 , 60 ]. Furthermore, an Irish study investigating physician attitudes towards mobility counselling found an association between considering activity counselling your role and providing this counselling [ 60 ], and revealed a lack of physician training in mobility.…”
Section: Discussionmentioning
confidence: 99%
“…Appendix B provides legends for all the tables in the paper. Twelve (12) of the 34 studies in this review, explored the perceptions of HCPs practising in Europe [53,[63][64][65][66][67][68][69][70][71][72][73], 10 were conducted in Australia and New Zealand [31,51,69,[74][75][76][77][78][79][80], five each from the UK [52,[81][82][83][84] and USA [85][86][87][88][89], two from Africa [75,90], and one from India [91]. The study designs were varied with 20 of the 34 included studies employing a cross sectional design [31,[65][66][67][68][70][71][72][73][74]76,79,…”
Section: Study Characteristicsmentioning
confidence: 99%